Forest and Land Fire Management in Indonesia: Unveiling the Implementation Gaps of Law No. 32 of 2009 in Palembang - Bayu Arya Sakti; Rodiyah; Cahya Wulandari (HM Publisher, 2025)
Forest and land fires (Karhutla) pose a significant environmental threat in Indonesia, particularly in Palembang. Law No. 32 of 2009 on Environmental Protection and Management provides a framework for fire prevention and mitigation. This study evaluated the law's implementation effectiveness in addressing Karhutla in Palembang. A socio-legal approach was employed, utilizing primary data from interviews with key informants (government officials, law enforcement, community leaders, and residents affected by fires) and secondary data from legal documents, reports, and academic literature. Qualitative data analysis techniques were used to identify themes and patterns. The study revealed that Law No. 32 of 2009 has not been effectively implemented in Palembang. Weaknesses were identified in law enforcement, inter-agency coordination, resource allocation, and community engagement. While a clear legal framework and stakeholder support exist, implementation is hindered by limited resources, inadequate sanctions, and low public awareness. In conclusion, to improve Karhutla management, strengthening law enforcement, enhancing inter-agency coordination, increasing public legal awareness, and ensuring adequate resource allocation are crucial.